Marasmius beijingensis (Marasmiaceae, Agaricales), a radicant species from China - Deng, Chunying; Huang, Youpu; Wang, Jing; Li, Taihui (Phytotaxa, 2025)
An interesting taxon of genus Marasmius was collected several times from Beijing, China. It is characterized by its small basidiomata, orange convex pileus, long and radicant stipe, hymeniform pilepellis of Globulares-type smooth cells , small cheilocystidia, and ellipsoid basidiospores measuring about 8.4 × 5.3 μm. Morphological and molecular analyses confirmed it as a new species. It is therefore introduced as M. beijingensis sp. nov. Comprehensive descriptions, illustrations, phylogenetic analysis results and comparison with similar taxa are provided.